Does corporate social responsibility initiative restrain young people from irregular migration in sub-Saharan Africa? Evidence from Nigeria's oil producing communities - Joseph I. Uduji; Elda N. Okolo-Obasi (African Governance and Development Institute (AGDI), 2020)
Purpose -The purpose of this paper is to critically examine the multinational oil companies (MOCs) corporate social responsibility (CSR) initiatives in Nigeria. Its special focus is to investigate the impact of the global memorandum of understanding (GMoU) on irregular migration urge of rural youths in the oil producing communities. Design/methodology/approach - This paper adopts a survey research technique, aimed at gathering information from a representative sample of the population, as it is essentially cross-sectional, describing and interpreting the current situation. A total of 2100 households were sampled across the Niger Delta region of Nigeria. Findings - The results from the use of a combined propensity score matching and logit model indicate that GMoU model has made significant impact in dissuading young people from irregular migration drive. Practical implications - This implies that if the MOCs increase the CSR intervention on young development initiatives that focus on creation of jobs and provision of financial and other resources that support local entrepreneurs, the push factors that compel youth irregular migration in sub-Saharan Africa would be deterred. Social implications - The fight against irregular migration of African youths and subsequent demise by sea, deserts and along the Mediterranean route can only succeed if cluster development boards (CDBs) of GMoUs are able to draw on young people to participate fully in the CSR intervention plans and programmes. Originality/value - This research adds to the literature on multinational enterprises' CSR initiatives in sub-Saharan Africa and rationale for demands for social projects by host communities. It concludes that business has an obligation to help in solving problems of public concern.
Keywords: 330; African youth; irregular migration; corporate social responsibility; multinationaloil companies; push factors; sub-Saharan Africa